2018
DOI: 10.1074/jbc.ra118.004188
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the heterodimeric complex of the nuclear receptors FXR and RXR

Abstract: Farnesoid X receptor (FXR) is a member of the family of ligand-activated nuclear receptors. FXR plays critical roles in maintaining many metabolic pathways, including bile acid regulation and glucose and lipid homeostasis, and forms a heterodimeric complex with the retinoid X receptor (RXR). Despite the important roles of the FXR/RXR heterodimerization in human physiology, the molecular basis underlying the FXR/RXR interaction is still uncertain in the absence of a complex structure. Here, we report the hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 36 publications
1
27
0
1
Order By: Relevance
“…In this study, we provide a structural and biochemical characterization of farnesoid X receptor in complex with its obligate heterodimer partner RXR␣. In agreement with previous studies, especially a recent FXR/RXR heterodimer structure with known FXR ligand WAY-362450 (27), we observed that FXR/ RXR heterodimer has the similar heterodimer interface with other RXR heterodimers. Our structural data provide an allosteric mechanism in which communications across the dimer interface, together with the two respective agonists, enhance the affinity of FXR and RXR for binding to individual LXXLL motifs.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we provide a structural and biochemical characterization of farnesoid X receptor in complex with its obligate heterodimer partner RXR␣. In agreement with previous studies, especially a recent FXR/RXR heterodimer structure with known FXR ligand WAY-362450 (27), we observed that FXR/ RXR heterodimer has the similar heterodimer interface with other RXR heterodimers. Our structural data provide an allosteric mechanism in which communications across the dimer interface, together with the two respective agonists, enhance the affinity of FXR and RXR for binding to individual LXXLL motifs.…”
Section: Discussionsupporting
confidence: 93%
“…Even though the FXRα/RXRα heterodimer binds to the consensus IR-1 (IR spaced by 1 base pair) sequence with the highest affinity, this complex also binds to and activates a variety of other FXREs in conjunction with transcriptional co-activators or co-repressors that coordinate either gene activation or repression following post-translational modifications of histones and non-histone proteins. Overviews of FXRα structure, activation, interaction with RXRα, and dynamically-controlled target gene regulation have been published previously [ 22 , 23 , 24 , 25 ].…”
Section: Structure-activity Relationship Of Bile Acids and Bile Acmentioning
confidence: 99%
“…In permissive heterodimers (e.g., PPAR/RXR and LXR/RXR), ligand binding to either partner can mediate their activities. While in non-permissive heterodimers (e.g., VDR/RXR and RAR/RXR), the heterodimer remains silent if only RXR is bound, hence, ligand binding to the partners of RXR is a prerequisite for activation (14,15). While permissive heterodimers seem to be lipid sensors that are regulated by many metabolic pathways (PPAR, LXR), non-permissive ones most likely respond to the classical endocrine steroid (ER) and non-steroid (RAR) factors (16).…”
Section: The Nuclear Receptorsmentioning
confidence: 99%